Problem solving : a handbook for teachers - Krulik, Stephen; Rudnick, Jesse A. (Boston : Allyn and Bacon, 1980)
Problem Solving: A Handbook for Senior High School Teachers.
Includes bibliography.
Keywords: Problem solving; Mathematics -- Study and teaching (Elementary).